Educational strategy I Learn at Home and virtual mediation in learning of schoolchildren in the Ancash region of Peru - Ramírez Julca, Máximo; Bringas Salvador, Jorge Luis; Ramírez Cerna, Johana Milagritos; Solís Cespedes, Pedro Aníbal; Hijar Hernández, Víctor Daniel (Journal of the University of Zulia, 2022)
The objective was to analyze the educational strategy I learn at home and virtual mediation, as an adequate and efficient response to face the educational problem generated by the COVID-19 pandemic in the Ancash region of Peru. The research was applied, at a quasi-experimental level. The universe of the population includes the parents of seven public institutions. The study sample was all 320 parents, with the application of the census method. It was evidenced that teachers and students have made use of the official platform of the Ministry of Education, for teaching-learning, using radio, television, mobile devices, which has facilitated asynchronous work. The virtual strategy has allowed teacher-student interaction, facilitating the use of classes recorded in videos and audios, allowing the subjects to be developed and better controlled, which has allowed knowing the relationship between the I learn at home strategy and virtual mediation. to complete the school year.